Anatomy, histochemistry, and immunohistochemistry of the olfactory subsystems in mice - Barrios, Arthur W.; Núñez, Gonzalo; Sánchez Quinteiro, Pablo; Salazar, Ignacio (Frontiers in Neuroanatomy, 2014)
The four regions of the murine nasal cavity featuring olfactory neurons were studied anatomically and by labelling with lectins and relevant antibodies with a view to establishing criteria for the identification of olfactory subsystems that are readily applicable to other mammals. In the main olfactory epithelium and the septal organ the olfactory sensory neurons (OSNs) are embedded in quasi-stratified columnar epithelium; vomeronasal OSNs are embedded in epithelium lining the medial interior wall of the vomeronasal duct and do not make contact with the mucosa of the main nasal cavity; and in Grüneberg’s ganglion a small isolated population of OSNs lies adjacent to, but not within, the epithelium. With the exception of Grüneberg’s ganglion, all the tissues expressing olfactory marker protein (OMP) (the above four nasal territories, the vomeronasal and main olfactory nerves, and the main and accessory olfactory bulbs) are also labelled by Lycopersicum esculentum agglutinin, while Ulex europaeus agglutinin I labels all and only tissues expressing Gi2 (the apical sensory neurons of the vomeronasal organ, their axons, and their glomerular destinations in the anterior accessory olfactory bulb). These staining patterns of UEA-I and LEA may facilitate the characterization of olfactory anatomy in other species. A 710-section atlas of the anatomy of the murine nasal cavity has been made available on line.